How Can Better Cooperation Between the United Nations Security Council and the United Nations General Assembly Advance Global Peace and Security? - Seung, Yuna Y (Technium Social Sciences Journal, 2025)
This paper aims to investigate how enhanced cooperation between the United Nations Security Council (UNSC) and the United Nations General Assembly (UNGA) can strengthen global peace and security in an increasingly polarized international system. While the former organ does hold binding enforcement authority, its current decision-making processes are currently constrained by the veto power of the Permanent 5 (P5) member states, resulting in institutional paralysis during urgent crises. Drawing on a mixed-methods approach with the UN Charter, the 1950 Uniting for Peace Resolution, and comparative case studies of the Korean War between North and South Korea (1950-1953) and the Russo-Ukrainian War (2014-present), this paper assess how the UNGA-led initiatives can compensate for inaction within the UNSC. The findings demonstrate that although the UNGA resolutions lack legal enforcement mechanisms, they still play a crucial role in restoring legitimacy and enabling quicker diplomatic or humanitarian responses when the UNSC faces deadlock. However, the absence of formal structural mechanisms between the two organs limits the coherence and long-term impact; therefore, to address this, this paper recommends three feasible reforms: establishing a Joint Crisis Council (JCC), adopting UNGA co-endorsement for peacekeeping mandates, and codifying procedures for declaring UNSC paralysis during mass-atrocity situations. In essence, strengthening the linkages between the inter-organs can enhance the United Nations’ capacity as a whole to act more decisively and legitimately during global crises.